Evaluation of a Laparoscopic Multi-approach Training for Obstetrics and Gynecology Residents - Maranhao, Débora Davalos Albuquerque; Barison, Gustavo Anderman Silva; Alvarenga-Bezerra, Vanessa; Ferreira, Laís Assenheimer de Paula; Schindler Leal, Anucha Andrade; Moretti-Marques, Renato; Podgaec, Sergio; Zlotnik, Eduardo; Gomes, Mariano Tamura Vieira (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Objective To analyze the applicability and efficiency of a multi-approach laparoscopic training in improving basic laparoscopic skills of obstetrics and gynecology (OBGYN) residents.Methods Cross-sectional, observational and descriptive study, developed at the Experimentation and Surgery Training Center (CETEC, in the Portuguese acronym) of the Hospital Israelita Albert Einstein with OBGYN residents. Theoretical and practical tests were applied to 24 OBGYN residents to assess their laparoscopic skills before and after their participation in an 8-week course. The course involved theoretical lectures and practical laparoscopic surgery exercises developed using rubber models, black boxes, virtual simulators and animal models (pigs).Results There was an overall improvement in the ability of the residents, with an increase in the number of correct answers in the theoretical evaluation and decrease in the time needed to perform practical tests (needle holder assembly and laparoscopic node). The course was evaluated by the students as highly relevant for both improving their surgical skills and motivating them to continue practicing.Conclusion Laparoscopic training using multiple approaches resulted in significant improvement of surgical skills with a high satisfaction level of the participants. Further studies are still needed to measure the long-term retention of these acquired skills.
Keywords: medical education; laparoscopic surgery; residency; training